Hubungan Kematangan Emosi dan Dukungan Sosial dengan Penyesuaian Diri Perempuan Kawin Tangkap - Melkianus, Chintya; Santi, Dyan Evita; Kusumandari, Rahma (Jurnal Humaniora dan Ilmu Pendidikan, 2025)
Purpose: This study aims to understand how emotional maturity and social support affect the ability of women to adapt after experiencing the kawin tangkap (Pitti Rambang) tradition in Sumba Island. Methodology/approach: The research used a quantitative correlational method. Participants were women from Sumba Island who had experienced the kawin tangkap tradition, selected using purposive sampling. Three psychological scales were used to measure emotional maturity, social support, and self-adjustment. Data were analyzed using Pearson correlation and multiple regression analysis. Results/findings: The study found a positive relationship between emotional maturity and self-adjustment (r = 0.628; p < 0.01), and between social support and self-adjustment (r = 0.587; p < 0.01). Together, emotional maturity and social support significantly contributed to self-adjustment (R² = 0.521; F = 24.138; p < 0.01). Conclusion: Emotional maturity and social support are crucial in helping women adapt after experiencing the kawin tangkap tradition. Strengthening these factors can enhance resilience and support women in overcoming psychological challenges associated with oppressive cultural practices. Limitations: The study only involved women who had experienced kawin tangkap and used a purposive sampling method, which may limit the generalizability of the findings to other cultural or regional contexts. Contribution: This study contributes to the field of community psychology and cultural studies by highlighting the importance of emotional and social factors in helping women adapt to culturally oppressive traditions. It can guide the development of culturally sensitive psychosocial support programs, especially for women in traditional or rural communities